Director-generals' human and social capital, and management performance of farmers' cooperatives: Evidence from China's Fujian - Bin Liu; Zhongbin Li (International Journal of Management and Economics, 2018)
Purpose - This study aimed to assess the impact of director-generals' human and social capitals on the organizational performance of farmers' cooperatives in Fujian Province. Design/Methodology/Approach - Questionnaire survey data of 303 standard cooperatives in nine cities of Fujian Province were statistically analyzed. Findings - We identified that director-generals' human and social capitals affect all four dimensions of cooperative performance, through the mediating role of management effectiveness. Practical Implications - We offer suggestions and measures for improving cooperatives' performance by enhancing the human and social capitals of director-generals. Based on China's national conditions, we propose measures to improve director-generals' human and social capitals by the Internal trust, Government policy support, and Business network (IGB) model, which emphasizes establishing a social network of cooperatives' director-generals, accumulating social capital, and promoting cooperative development through internal members, government departments, and commercial organizations.
Keywords: Q13; J24; 650; Farmer cooperatives; Director-general; Human capital; Social capital; Operational performance